2005
DOI: 10.1108/00483480510571897
|View full text |Cite
|
Sign up to set email alerts
|

Facets and dimensions of cross‐cultural adaptation:refining the tools

Abstract: Purpose -The management literature on cross-cultural adaptation has used a conceptualisation and measurement approach developed by Black and Stephens. Their work has led to significant development in the field. Now it is time to move beyond and use a more refined tool. This paper proposes such a tool and compares its characteristics with those of the older instrument. Design/methodology/approach -The paper is based on a sample of 204 expatriates, who were surveyed using the older and the proposed instrument. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 56 publications
(97 reference statements)
2
39
0
4
Order By: Relevance
“…En primer lugar se aplicó un cuestionario online de elaboración propia, validado para esta investigación, con base en las dimensiones propuestas por Haslberger (2005) relativas al proceso de ajuste a la comunidad receptora durante experiencias de transculturación. Este cuestionario incluyó 26 ítems distribuidos en seis bloques: (A) Perfil del alumno, (B) Movilidad, (C) Redes Sociales, (D) Adaptación transcultural, (E) Aprendizaje intercultural y (F) Emociones.…”
Section: Técnicas Y Procedimientounclassified
“…En primer lugar se aplicó un cuestionario online de elaboración propia, validado para esta investigación, con base en las dimensiones propuestas por Haslberger (2005) relativas al proceso de ajuste a la comunidad receptora durante experiencias de transculturación. Este cuestionario incluyó 26 ítems distribuidos en seis bloques: (A) Perfil del alumno, (B) Movilidad, (C) Redes Sociales, (D) Adaptación transcultural, (E) Aprendizaje intercultural y (F) Emociones.…”
Section: Técnicas Y Procedimientounclassified
“…The questionnaires were sent together with a cover letter by email to the human resources manager for distribution to their construction company executive expatriates overseas. As proposed by Haslberger [13] this method is the best and effective way in getting responses from the expatriates. At present, distributing questionnaire using email is the most suitable method and get a high return rate as proposed by Babbie [2].…”
Section: Samplementioning
confidence: 99%
“…At present, distributing questionnaire using email is the most suitable method and get a high return rate as proposed by Babbie [2]. Haslberger [13] and Piaw [24] showed the snowball sampling method was used to obtain respondents. When the respondents replied, a letter of appreciation was sent to them.…”
Section: Samplementioning
confidence: 99%
“…In the cross-cultural adaptation, cultural novelty has played an important role for a long time. Research has indicated a negative influence of cultural novelty on adaptation outcomes [9]. Young defined cross-cultural adaptation is "as the entirety of the phenomenon of individuals who, on relocation to an unfamiliar socio-cultural environment, strive to establish and maintain a relatively stable, reciprocal, and functional relationship with the environment" [6].…”
Section: Cross-cultural Adaptationmentioning
confidence: 99%